The Importance of Building Spiritual Health by The Application of Islamic Psychology in Life - Fatimah Fatimah; Masyitoh Masyitoh; Suherman Suherman; Nur Romdhona; Dihartawan Dihartawan (Indonesian Journal of Islam and Public Health, 2022)
Spiritual intelligence is the ability to interpret and find the purpose of life by using one's own inner resources and strength due to attachment to God. Aspects measured include self-awareness, idealism, effort in dealing with difficulties, openness, assertiveness, critical thinking or asking why, and responsiveness. Humans who reach spiritual maturity will prefer friendship with all. In addition, the human being is very liked by the people around him, because this human who has matured spiritually is able to provide fresh air that cools the people around him. Those who have spiritual intelligence, will not feel hopeless or tired in the activities they do. The Islamic conception of spirituality is different from the western conception which distinguishes spirituality from religion. The concept of ad-din is the umbrella of spirituality. In the context of Islam, there is no spirituality without religious beliefs, teachings, and deeds. Religion is a system of life (way of life) that provides a spiritual path for the salvation of the world and the hereafter.